A cultural inquiry into ambidexterity in supervisor–subordinate relationship. Issue 2 (19th January 2020) - Xing, Yijun; Liu, Yipeng; Tarba, Shlomo; Wood, Geoffrey
Abstract: Guanxi is a key construct in Chinese management and organization scholarship, and has been widely treated as a relational concept. However, it is necessary to gain a nuanced and contextualized understanding of Guanxi to examine its cultural antecedents by resorting to traditional Chinese cultures. We draw upon the emerging literature on ambidexterity and HRM to examine Guanxi in the context of superior–subordinate relationship and conceptualize ambidextrous Guanxi as possessing two orientations: relational and merit - based . To investigate ambidextrous Guanxi in the context of superior–subordinate relationship, we perform in-depth, qualitative narrative interviews with managers in Chinese state-owned enterprises. Our results reveal three dimensions: loyalty, dependence upon supervisor and work priority by which ambidextrous Guanxi enables, facilitates and accommodates the tension between individual career advancement and commitment to the organization. From a cultural inquiry perspective, we argue that Confucianism and Legalism, as cultural antecedents of ambidextrous Guanxi, shed light on its contemporary managerial implications. Our findings suggest that Guanxi can be considered as a strategic HR asset and enhance performance outcomes both at the individual level (career advancement) and the organizational level (commitment to the rganization).